THU0025 ANALYSIS OF POTENTIAL INTERACTIONS BETWEEN TENOCYTES AND SYNOVIAL FIBROBLASTS AFTER STIMULATION WITH CYTOKINES EXPRESSED WITHIN THE SYNOVIO-ENTHESAL COMPLEX. (June 2019) - Dechant, Felix; Frommer, Klaus; Millar, Neal L; Mcinnes, Iain; Rehart, Stefan; Müller-Ladner, Ulf; Neumann, Elena
Abstract : Background: Psoriatic arthritis (PsA) is frequently associated with enthesitis. It has been proposed that inflammatory processes at the synovio-enthesal complex are involved in the pathogenesis of inflammatory arthritides including especially PsA. Besides IL-1β and TNF-α, IL-15, IL-23 and IFN-γ are cytokines expressed within the synovium, tendons and entheses and some of which are already used as therapeutic targets. While synovial fibroblasts (SF) are known key effector cells of cartilage destruction in inflammatory arthritides such as RA, tenocytes are a major component of tendons and entheses and play a central role in tendon inflammation observed in PsA. Objectives: To investigate whether PsASF and tenocytes show significant interactions while being stimulated with the above cytokines alone as well as in combination with the aim to find out whether these may contribute to the pathogenesis of PsA. Methods: SF were isolated from patients with PsA undergoing joint surgery. Human tenocytes were acquired commercially and isolated from hamstring tendon tissue of patients undergoing hamstring tendon ACL reconstruction. PsASF and tenocytes were stimulated with IL-1β, TNF-α, IFN-γ, IL-15 and IL-23 alone and in combination. Direct cell co-culture experiments were performed at a 1:1 ratio of both cell types in parallel to experiments with single cell type cultures. IL-6 levels were measured by ELISA to quantify the immunological activation of the cells. Results: PsASF as well as tenocytes showed strong responses to IL-1β (tenocytes ↑173-fold, n=3; PsASF ↑56-fold, n=3) and TNF-α (tenocytes ↑10-fold, n=3; PsASF ↑9-fold, n=3) stimulation regarding IL-6 secretion. IFN-γ alone had only minimal effects on both cell types but acted synergistically when applied together with IL-1β (tenocytes ↑218-fold, n=3; PsASF ↑129-fold, n=3) and TNF-α (tenocytes ↑24-fold, n=3; PsASF ↑19-fold, n=3). IL-15 and IL-23 alone showed no effect but the data suggest a small antagonistic effect against IL-1β (tenocytes IL-15 ↓21%/IL-23 ↓27%, n=3; PsASF IL-23 ↓19%, n=3) and TNF-α induced IL-6 secretion. Overall, PsASF and tenocytes showed similar responses in the single cell type stimulation experiments. Co-culturing PsASF and tenocytes did not reveal any synergistic or antagonistic interactions in regards to any of the cytokines used. Conclusion: Our data suggest that tenocytes and PsASF do not interact in a way that would promote inflammation within the synovio-enthesal complex. Also, as far as the induction of IL-6 is concerned, PsASF and tenocytes are not major target cells of IL-15 and IL-23. IFN-γ, however, may be able to promote inflammation in combination with other cytokines in both cell types. Disclosure of Interests: Felix Dechant: None declared, Klaus Frommer: None declared, Neal L Millar: None declared, Iain McInnes Grant/research support from: AstraZeneca, Celgene, Compugen, Novartis, Roche, UCB Pharma, Consultant for: AbbVie, Celgene, Galvani, Lilly, Novartis, Pfizer, UCB Pharma, Stefan Rehart: None declared, Ulf Müller-Ladner Grant/research support from: Projekt supported by an unrestricted educational grant from Celgene GmbH., Elena Neumann: None declared